The Emancipatory Critical Paradigm in Islamic Religious Education as an Effort to Form a Tolerant and Multicultural Attitude - Thoyibah Thoyibah; Muhlisin Muhlisin; Moch. Sugeng Solehudin; Fatah Syukur; Asnalia Rokhmah (Academia Open, 2026)
General Background The persistence of religious intolerance and exclusivism within educational contexts reveals unresolved pedagogical challenges in religious education systems. Specific Background In Islamic Religious Education, learning practices remain largely normative–doctrinal and transmissive, limiting students’ dialogical engagement and critical awareness within pluralistic social realities. Knowledge Gap Although tolerance and multiculturalism have been widely discussed, few studies systematically integrate a critical–emancipatory paradigm into the ontological, epistemological, and axiological foundations of Islamic Religious Education. Aims This study analyzes the relevance and conceptual contribution of the critical–emancipatory paradigm as an alternative pedagogical framework for Islamic Religious Education in fostering tolerant and multicultural attitudes. Results Using qualitative library research grounded in critical theory, the findings demonstrate that the critical–emancipatory paradigm is theologically and pedagogically compatible with Islamic values such as justice, human dignity, and rahmatan lil ‘alamin, while redirecting learning from indoctrinative models toward dialogical, reflective, and contextual practices. Novelty This article constructs an integrative conceptual framework linking the critical–emancipatory paradigm with the ontological, epistemological, and axiological dimensions of Islamic Religious Education. Implications The study contributes theoretically to critical Islamic education discourse and offers a coherent pedagogical orientation for developing tolerance, social empathy, and multicultural competencies within Indonesia’s pluralistic educational context. Highlights: Normative–doctrinal learning practices are conceptually linked to weak internalization of plural social values. Dialogical and reflective pedagogy aligns with Islamic theological principles of justice and human dignity. Ontological, epistemological, and axiological integration provides a unified framework for pedagogical renewal. Keywords: Islamic Religious Education, Critical Emancipatory Paradigm, Tolerance, Multiculturalism, Critical Pedagogy